2022
DOI: 10.3390/methane1030017
|View full text |Cite
|
Sign up to set email alerts
|

Enteric Methane Emission from Sheep Fed with Rhodes Grass Hay (Chloris gayana) Alone or Supplemented with Dried Distillers’ Grains with Solubles

Abstract: Livestock systems based on subtropical and tropical pastures are characterized by the low productivity of livestock due to the poor nutritional value of the forage (low nitrogen concentration and digestibility, and high fiber and lignin concentrations). These conditions lead to low productivity and, consequently, high absolute emissions of methane (CH4) per unit of product. Dry distilled grains with solubles (DDGS) are the main by-product resulting from ethanol production, and they are characterized by their h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…Comparison of emissions across experiments is more relevant when emissions are expressed in terms of CH 4 yield (e.g., g/kg DMI, g/kg DOMI, and on energy basis, MJ CH 4 /MJ GEI). The CH 4 yield found in this study (23.3-26.4 g/kg DMI) is within the range found by other studies in tropical environments with tropical low-quality forages (Hunter, 2007;Archimède et al, 2018;Costa et al, 2020;Gere et al, 2022). For example, Archimède et al (2018), reported CH 4 yields in the range of 15-29 g/kg DMI from sheep fed low quality C4 grasses; whereas Hunter (2007) and Gere et al (2022) reported even a higher CH 4 yield (31 g/kg DMI each) from cattle fed on Angleton grass and sheep fed on Rhodes grass hay (a forage similar to that used in the present study), respectively.…”
Section: Effects Of Gin Infection and Breed On Daily Methane Emission...supporting
confidence: 90%
“…Comparison of emissions across experiments is more relevant when emissions are expressed in terms of CH 4 yield (e.g., g/kg DMI, g/kg DOMI, and on energy basis, MJ CH 4 /MJ GEI). The CH 4 yield found in this study (23.3-26.4 g/kg DMI) is within the range found by other studies in tropical environments with tropical low-quality forages (Hunter, 2007;Archimède et al, 2018;Costa et al, 2020;Gere et al, 2022). For example, Archimède et al (2018), reported CH 4 yields in the range of 15-29 g/kg DMI from sheep fed low quality C4 grasses; whereas Hunter (2007) and Gere et al (2022) reported even a higher CH 4 yield (31 g/kg DMI each) from cattle fed on Angleton grass and sheep fed on Rhodes grass hay (a forage similar to that used in the present study), respectively.…”
Section: Effects Of Gin Infection and Breed On Daily Methane Emission...supporting
confidence: 90%
“…This positive effect was linked to an increased dry matter intake, as well as a higher digestibility and energy concentration in the diet. As a result, the study suggests that utilizing industrial byproducts as a supplement for low-quality diets could be a promising approach to mitigating methane emissions (Gere et al, 2022). In conclusion of studies discussed above which highlights various alternative forages and supplements that can positively influence the performance and health of livestock.…”
Section: Effect On Goat and Sheepmentioning
confidence: 84%